Taxonomic Study of Fish Fauna in Tishreen Lake (Euphrates River) - Al Majid, Zouhir (Latakia University Journal -Biological Sciences Series, 2019)
In this research, 24 fish species of were recorded in Tishreen Lake (Euphrates River), belonging to 18 genera belonging to 10 families (Cyprinidae, Salmonidae, Siluridae, Mugilidae, Mastacembelidae, Clariidae, Cichlidae, Atherinida). Cyprinidae family characterized bythe abundance of its species; 16 species represented in 9 gener. The most diverse genus was Barbus,when represented by 4 species ,while the other families were represented by one genus and one species. The Atherinaboyeri specie of Atherinidaewas recorded for the first time in this lake. في هذا البحث تم تسجيل 24 نوعاً من الأسماك في بحيرة تشرين(نهر الفرات) وهي تتبع 18 جنس تنتمي إلى 10 فصائلCyprinidae, Salmonidae,Siluridae, Mugilidae, Mastacembelidae ,Clariidae Cichlidae ,Atherinidae واتسمت الفصيلة الشبوطية بغزارة أنواعها حيث تم تسجيل 16 نوع تنتمي إلى 9 أجناس وكان أكثرها تنوعاً الجنس Barbus, حيث سجل 4 أنواع, أما الفصائل الأخرى فتمثلت كل منها بجنس واحد ونوع واحد. و قد سجل لأول مرة النوع Atherinaboyeri التابع للفصيلة Atherinidae بغزارة أفراده في البحيرة .